Directors' shareholdings and executive equity-based compensation influence on fraudulent financial reporting: Malaysia case / Noralizah Mohd Aliman - Mohd Aliman, Noralizah (2013)
The primary objective of this study is to investigate whether directors' shareholdings and executive equity-based compensation influence the occurrence of fraudulent financial reporting in Malaysia. This study employed a sample of 180 listed firm-year observations of Malaysian listed companies over the period 2003 to 2010. Specifically, the sample consists of 90 fraud firms, matched with 90 non-fraud firms. The sample of fraud firms was identified based on the announcement of fraud occurrence and breach of the listing requirement of Securities Commission and Bursa Malaysia. Employing the logistics regression approach, the findings show that directors' shareholdings have negative association with the occurrence of fraudulent financial reporting which indicate that the higher ownership level reduces the tendency of fraud to occur. The result also shows that the outstanding stock option available has positive association with fraud occurrence, suggesting that executive motivate to commit fraud to gain equity-based compensation. These results were robust even after controlling for firms specific factors, industry and year effects, and various specification tests. This study however, does not address other mechanisms of governance.